PENGARUH METODE PEMBELAJARAN TOTAL PHYSICAL RESPONSE TERHADAP KEMAMPUAN KOSAKATA BARU BAHASA INDONESIA YANG BAKU OLEH SISWA KELAS II SEKOLAH DASAR NEGERI NAIKOTEN 2 KOTA KUPANG - Moses Kopong Tokan; Maxsel Koro; Putra Zulkiflyn (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of the method total physical response on the new standard vocabulary of Indonesian in use by students in class II in Naikoten 2 Public Elementary School, Kupang City. This research uses a randomized pretest-posttest control group in a true experiment design. All students at SDN Naikoten 2 made up the population of this study, and all students in classes II-A (the control class) and II-B made up the sample (experimental class). For the purpose of this study, documentation, tests, and observations are used as data gathering methods. Using the Wilcoxon formula in the SPSS version 21 application, the hypothesis was tested, and if Asymp.Sig.(2-tailed) 0.05, H0 is rejected and H1 is accepted based on the analysis results.